Kajian Pembuatan Beras Analog Berbasis Tepung Komposit dengan Penambahan Konsentrasi Bubur Rumput Laut (Gracilaria sp.) dan Gliserol Monostearat - Damat Damat; Rizma Amalia Natazza; Vritta Amroini Wahyudi (Food Technology and Halal Science Journal, 2020)
Rice consumption is estimated to increase along with the increase in population every year. Analog rice is one alternative to functional food diversification and was expected to help reduce people's dependence on rice consumption. The addition of seaweed and glycerol monostearate in the study was intended to improve the shape of rice grains from previous studies which were sticky so that the shape of the rice was lost, enriching antioxidants and fiber from analog rice. The purpose of this study was to determine the interaction and effect of the addition of seaweed pulp extracts and glycerol monostearate to analog rice. The design of this study is a factorial randomized block design (RBD-F). Factor I is seaweed with 3 levels of concentration {1%, 2%, 3%}, factor II is glycerol monostearate with 4 levels of concentration {1%, 2%, 3%, 4%}. The results of the study the highest value on the water content of the addition of seaweed 3% by 7.51%; carbohydrate glycerol monostearate level of 1% was 91.78%; the antioxidant activity of rice and rice in seaweed concentration of 3% by 27.35% and 25.57%; The highest value of rice fiber and rice in the treatment of Seaweed 3% and GMS 3% by 1.53% and 1.63%. Organoleptic results in the form of appearance (5.33 = interesting), taste (4.44 = somewhat like), fondness (4.33 = somewhat like), aroma (2.67 = not fishy), and texture (2.33 = not sticky).